Rigor Mortis and News obtained by the Body's Scientific Reconstruction of the Turin Shroud Man - Bevilacqua M; Concheri G; Concheri S; Fanti G; Rodella S (Forensic Science Today - Peertechz Publications, 2018)
After various tentative to artistically build a tridimensional form of the Turin Shroud (TS) Man, the authors faced the problem of the scientific construction of a 3D model of this Man with an accuracy of the order of 1 cm. It is well known that the TS wrapped a human body heavily tortured, but it is not easy to build a 3D model starting only from the 2D information shown on two body images visible on a linen sheet and on the hypothesis that these images really corresponds to a real man wrapped in it. The study showed that, while the two TS body images (frontal and dorsal) seem to appear not coherent with the image of a human body because distorted in many parts, these two images are perfectly coherent with the distortions provoked by a man wrapped in this linen sheet. This model confirmed the evident rigor mortis of the human body and evidenced the particular posture corresponding to the position on the cross that also showed a rotation never detected previously of the human body around his spine. The study of this 3D model partially confi rmed previous results but also evidenced interesting news, like the position of the exit hole of the nail posed on the palm of the hand. The Gospels place the Resurrection in the early hours of Sunday, at least 36 hours after death. The effect of the preservation of rigidity up to this moment may be not consistent with the thanatochronological alterations expected in a man in the same pre-mortal clinical condition, but this problem has been solved by the "mixture of aloe and myrrh" that allowed the preservation of the corpse, thus prolonging the rigor mortis for tens of hours. In fact, this body seems not to have undergone any significant putrefactive phenomenon.